Іле Aлaтaуындa құрaмындa эндемик түр Oxytropis almaatensis кездесетін кейбір өсімдіктер қaуымдaстықтaрының сипaттaмaсы (ҚазҰУ хабаршысы. Экология сериясы, 2018)
The article presents geobotanical characteristics and floristic analysisof the communities with narrowly endemic species Oxytropis almaatensis, which found by us in the part of the spruce belt of the Trans-Ili Alataumountains in Big Almaty gorge. By the authors noted that Oxytropis almaatensis is really narrowly endemic plant that grows on loose scree slopeof the mountains and on the alluvial soils of mountain rivers. The plant occupies a limited area and its area is ruptured, even within the same gorge.However, living state of Oxytropis almaatensis in Trans-Ili Alatau mountaibs is good. Here can be found all life forms of the species, ranging fromseedlings and juveniles, ending by senile individuals. Moreover the plantsare blooming profusely and bear fruit annually. There is no direct threatsto the population of Oxytropis almaatensis, because of the whole area ofplant population is protected territory of Ili-Alatau National Park. However, loose scree on the slope of the mountains and alluvial sandy-gravellysoil of the valley of mountain river can be easily changed depending on thesnow cover thickness, the spring floods and summer floods characters. Taking this into consideration, the authors recommend to constantly monitoring those areas where the Oxytropis almaatensis populations were found,thus, to keep under control the population state.Key words: Dominant, subdominant, phytocoenosis, life form,hemicryptophyte, terofit, mesophyte, xerophyte.